Bio‐based polymers production in a kraft lignin biorefinery: techno‐economic assessment. (21st November 2017) - Dessbesell, Luana; Yuan, Zhongshun; Hamilton, Shawn; Leitch, Mathew; Pulkki, Reino; Xu, Chunbao (Charles)
Abstract: This paper presents a techno‐economic and risk analysis of a kraft lignin (KL) biorefinery (3000 tonne of KL·year ‐1 capacity), where KL is depolymerized to produce depolymerized kraft lignin (DKL) as a bio‐substitute to polyol and phenol for the production of bio‐based polymers (polyurethane and phenolic resins). Three scenarios were examined: (i) DKL as a phenol substitute, (ii) DKL as a polyol substitute, and (iii) oxypropylated depolymerized kraft lignin (Oxy‐DKL) a polyol substitute. The Net Present Value was calculated to compare these scenarios. To address the uncertainty risks in feedstock and product price, a sensitivity analysis and a Monte Carlo simulation were performed. Results show that DKL and Oxy‐DKL derived from the KL biorefinery are a feasible bio‐substitute for petroleum‐based polyols with a minimum selling price of 1440 and 1623 US$·t ‐1, respectively. However, DKL is likely not feasible when replacing phenol (minimum selling price of 1421 US$·t ‐1 ) due to the current low market price of phenol. The feasibility of the KL biorefinery is highly sensitive to the market prices of the products. Feedstock supply and market demand for lignin‐derived biopolyols are still uncertain; therefore, a supply chain design model is necessary for decision‐making. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd